2003
DOI: 10.1128/iai.71.2.682-689.2003
|View full text |Cite
|
Sign up to set email alerts
|

A/J Mice Are Susceptible and C57BL/6 Mice Are Resistant toListeria monocytogenesInfection by Intragastric Inoculation

Abstract: Previous studies demonstrated that the innate resistance of mice to Listeria monocytogenes infection by intravenous or intraperitoneal inoculation is regulated principally by the Hc locus on mouse chromosome 2. The A/J and C57BL/6 mouse strains were identified as prototype L. monocytogenes-susceptible and -resistant strains, respectively. In the present study, we compared the relative susceptibilities of A/J and C57BL/6 mice to intragastric (i.g.) inoculation with L. monocytogenes. The results of our study ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 31 publications
(35 reference statements)
5
54
1
1
Order By: Relevance
“…Further, L. monocytogenes also does not appear to target the murine brain stem or the fetoplacental unit, even following intravenous injection (121,122). L. monocytogenes strains do vary in their ability to cause systemic infection in intragastrically infected mice (38), and some strains of mice (A/J) are also more susceptible than others (C57BL/6) to intragastric infection (39). However, as a consequence of the biological differences in murine and human L. monocytogenes translocation across the intestinal barrier, data from mouse infection experiments may underestimate a given strain's human virulence following oral infection.…”
Section: Stress Response Alternative Sigma Factorsmentioning
confidence: 99%
“…Further, L. monocytogenes also does not appear to target the murine brain stem or the fetoplacental unit, even following intravenous injection (121,122). L. monocytogenes strains do vary in their ability to cause systemic infection in intragastrically infected mice (38), and some strains of mice (A/J) are also more susceptible than others (C57BL/6) to intragastric infection (39). However, as a consequence of the biological differences in murine and human L. monocytogenes translocation across the intestinal barrier, data from mouse infection experiments may underestimate a given strain's human virulence following oral infection.…”
Section: Stress Response Alternative Sigma Factorsmentioning
confidence: 99%
“…Epidemic strains were significantly more invasive as a group than environmental strains and caused extensive hemorrhage in the intestines of some mice. A/J mice are relatively inefficient at mobilizing inflammatory cells, initiate a slower and less exuberant production of inflammatory cytokines, and have diminished antiListeria phagocytic activity; however, they are not considered an immunodeficient strain (6,10,14). Additionally, the macrophagemediated immune response of younger mice against L. monocytogenes infection is not fully developed (7,20).…”
Section: Susceptibility Of Mice From Different Vendors To L Monocytomentioning
confidence: 99%
“…Furthermore, studies describing intragastric infection of mice or guinea pigs required relatively high numbers of bacteria (10 9 CFU) (2,3,16,18,26). Recently, an A/J mouse model in which intragastric inoculation was used was described by Czuprynski et al (6). It was found that 6-to 8-week-old A/J mice develop systemic infection following intragastric inoculation by using numbers of organisms similar to what is detected in L. monocytogenescontaminated food products.…”
mentioning
confidence: 99%
“…It has been shown that prfA mutants are not able to invade and multiply within mammalian cells in vitro and are avirulent when inoculated intravenously or intraperitoneally into mice (6,14,15,30,33). However, there is little information regarding how prfA affects the ability of L. monocytogenes to compete and survive in the gastrointestinal (GI) tract, translocate across the intestinal mucosa, and disseminate to other organs where it can cause systemic disease.Our laboratory has developed a mouse model for gastrointestinal listeriosis in which the genetically susceptible A/J mouse strain develops significant systemic infection following peroral inoculation with L. monocytogenes at a challenge dose (i.e., approximately 10 6 CFU) that can occur in contaminated food products (8,9). In the present study, we used this model to investigate how the prfA gene affects the virulence of L. monocytogenes in the gastrointestinal tract of mice.…”
mentioning
confidence: 99%
“…Our laboratory has developed a mouse model for gastrointestinal listeriosis in which the genetically susceptible A/J mouse strain develops significant systemic infection following peroral inoculation with L. monocytogenes at a challenge dose (i.e., approximately 10 6 CFU) that can occur in contaminated food products (8,9). In the present study, we used this model to investigate how the prfA gene affects the virulence of L. monocytogenes in the gastrointestinal tract of mice.…”
mentioning
confidence: 99%